Place of istmusectomy in thyroid tumors management: experience of National Medical Research Center of Endocrinology - P. A. Nikiforovich; D. G. Beltsevich; M. S. Berlovich (Опухоли головы и шеи)
Introduction. Given the relatively favorable prognosis in highly differentiated thyroid cancer and improvement in diagnosis of the disease, an assessment of patients’ life quality and risk of developing surgical complications comes to the fore. The lack of studies and recommendations regarding the volume of thyroid resection in patients with tumors limited by its isthmus does not allow determining what the surgery volume is optimal, especially for patients at low risk of relapse.Aim. To determine the advantages and disadvantages of isthmusectomy as a method of treating nodular pathology of the thyroid gland with suspected cancer, as well as indications for such surgery and its limitation on the basis of experience of the National Medical Research Center for Endocrinology and the scientific data available to date.Materials and methods. The study included 32 patients with nodal formation in the thyroid gland isthmus, who underwent istmusectomy; the postoperative follow-up period for them was 6 months or more.Results. In the preoperative phase, thyroid cancer was suspected in 19 (56.3 %) cases; all patients were classified as a low risk of relapse. According to a morphological study, the diagnosis of thyroid cancer was confirmed in 22 patients; all of them had the stage I disease. According to the dynamic risk stratification of the American Thyroid Association (ATA), 21 (95.5 %) patients with verified thyroid cancer were assigned to the low risk of recurrence, 1 (4.5 %) to the high risk of recurrence due to presence of vascular invasion and aggressive morphological tumor subtype (the patient underwent a final thyroidectomy). Over the entire observation period, no cases of recurrence were recorded, that indicates a high quality of preoperative examination when selecting patients for isthmusectomy and the effectiveness of the surgical intervention.Conclusion. The results of the study allow us to consider isthmusectomy as a safe and effective method of surgical treatment of patients with nodal formations of the thyroid gland localized in its isthmus. Further studies with a longer follow-up period are needed to fully analyze effectiveness of this method.